The Influence of Individual and Team Mindfulness on Work Engagement - Liu, Shengmin; Xin, Huanhuan; Shen, Li; He, Jianjia; Liu, Jingfang (Frontiers in Psychology, 2020)
Mindfulness is a kind of metacognitive practice on workplace. Drawing on conserve of resources theory, we test a moderated mediating model that how and when employee mindfulness has benefits on work engagement. Via data analysis of 311 employees from 83 teams at different times, this study focuses on the relationship between employee mindfulness and work engagement, as well as the moderating effect of team mindfulness and the mediating effect of recovery level. The results from this multi-wave field study show that employee’s individual mindfulness plays the positive influence on work engagement, and recovery level plays a mediating role. Team mindfulness positively moderates the relationship between individual mindfulness and work engagement. This conclusion may bridge the relationship between mindfulness and work engagement theory.